ANALISIS TINGKAT KEPUASAN MASYARAKAT TERHADAP PEMBANGUNAN JALAN (STUDI KASUS: PERUMAHAN BHAYANGKARA PERMAI (POLDA) BUPER, KECAMATAN HERAM, KOTA JAYAPURA) - Samosir, Rasi Kasim; Siregar, Anggrainy Togi Marito; Purba, Rispah; Tommi, Tommi; Sitompul, Fanny Kristin Tantyah; Lubis, Rizal Arifin (Ensiklopedia Sosial Review, 2025)
Abstract: here has been no evaluation related to the level of public satisfaction with the construction of roads in the Bhayangkara Permai (Polda) Buper Waena housing complex RT 005 RW 001, Waena Village, Heram District, Jayapura City. This study aims to determine the level of public satisfaction with the construction of roads in the Bhayangkara Permai (Polda) Buper Waena housing complex, Waena Village, Heram District, Jayapura City. Data collection using saturated sampling techniques to 20 respondents who live in the Bhayangkara Permai (Polda) Buper Waena housing complex RT 005 RW 001, Waena Village, Heram District, Jayapura City. The research variables were compiled using the Kanzei method which was adjusted to the Public Satisfaction Index (IKM) variable of the Kepmen PAN Number 25 of 2004. The measurement results obtained the overall service element was very satisfied with an average of 3,575. Based on the results obtained, "Friendliness of officers involved in road construction" obtained the lowest average satisfaction value (ranking 1) with an average value of service elements of 3.45 on a scale of 1 to 4. While "Responsibility of officers in carrying out road construction" has the highest average satisfaction value (ranking 10). In order for public satisfaction to increase further, the government should carry out regular maintenance on the roads that have been built. In addition, continue the construction of roads in each alley and drainage in the Bhayangkara Permai (Polda) housing complex, Buper Waena, Waena Village, Heram District, Jayapura City.Keywords: Kanzei, Buper Waena, road construction